Cardiovascular PET-CT imaging: a new frontier?. Issue 7 (July 2016) - Adamson, P.D.; Williams, M.C.; Newby, D.E.
Abstract : Cardiovascular positron-emission tomography combined with computed tomography (PET-CT) has recently emerged as an imaging technology with the potential to simultaneously describe both anatomical structures and physiological processes in vivo . The scope for clinical application of this technique is vast, but to date this promise has not been realised. Nonetheless, significant research activity is underway to explore these possibilities and it is likely that the knowledge gained will have important diagnostic and therapeutic implications in due course. This review provides a brief overview of the current state of cardiovascular PET-CT and the likely direction of future developments.